Efek Pemberian Jus Buah Jambi Biji Daging Merah (Psidium guajava L.) Terhadap Aktivitas Dan Kapasitas Fagositosis Pada Mencit Putih Jantan - Yufri Aldi; Widya Nengsih; Zet Rizal (STIFARM Padang, 2012)
Reasearch about the effect of feeding guava red meat juice (Psidium guajava L.) on the activity and capacity of peritoneal macrophage phagocytic of white males mice has been done. The test sample is given orally for 7 days with a dose of 0.13 mL/20g BB, 0.26 mL/20g BB and 0.52 mL/20g BB, while the control group was given only distilled water. On the eighth day the bacteria Staphylococcus aureus was injected to mice intraperitonially. Result of this experiment showed that guava juice can increased activity and capacity of macrophage (P<0.05).Psidium guava L ,phagocyticed, white mice